A global call to action to improve the care of people with fragility fractures. Issue 8 (August 2018) - Dreinhöfer, K.E.; Mitchell, P.J.; Bégué, T.; Cooper, C.; Costa, M.L.; Falaschi, P.; Hertz, K.; Marsh, D.; Maggi, S.; Nana, A.; Palm, H.; Speerin, R.; et al.
Abstract: The ageing of society is driving an enormous increase in fragility fracture incidence and imposing a massive burden on patients, their families, health systems and societies globally. Disrupting the status quo has therefore become an obligation and a necessity. Initiated by the Fragility Fracture Network (FFN) at a "Presidents' Roundtable" during the 5 th FFN Global Congress in 2016 several leading organisations agreed that a global multidisciplinary and multiprofessional collaboration, resulting in a Global Call to Action (CtA), would be the right step forward to improve the care of people presenting with fragility fractures. So far global and regional organisations in geriatrics/internal medicine, orthopaedics, osteoporosis/metabolic bone disease, rehabilitation and rheumatology were contacted as well as national organisations in five highly populated countries (Brazil, China, India, Japan and the United States), resulting in 81societies endorsing the CtA. We call for implementation of a systematic approach to fragility fracture care with the goal of restoring function and preventing subsequent fractures without further delay. There is an urgent need to improve: Acute multidisciplinary care for the person who suffers a hip, clinical vertebral and other major fragility fractures Rapid secondary prevention after first occurrence of all fragility fractures, including those in younger people as well as those in older persons, to prevent future fractures Ongoing post-acute care of people whose ability to function is impaired by hip and major fragility fractures To address this fragility fracture crisis, the undersigned organisations pledge to intensify their efforts to improve the current management of all fragility fractures, prevent subsequent fractures, and strive to restore functional abilities and quality of life.